ANALISIS MAKANAN ALAMI DALAM LAMBUNG DAN MIKROHABITAT LOBSTER PASIR (Panulirus homarus) FASE PUERULUS DI TELUK AWANG - Muhsinul Ihsan; Suhirman suhirman; Edi M Jayadi; Reza Sagista; Yuli Eka Hardianti; Wahyu Bintang Ilahi; Handa Muliasari; Lalu Achmad Tantilar Wangsajati Sukmaring Kalih (Jurnal Riset Akuakultur, 2019)
Pulau Lombok memiliki potensi dalam industrialisasi lobster. Aspek makanan alami larva perlu dipahami untuk mendukung pembenihan lobster. Tujuan penelitian ini untuk menganalisis makanan alami dalam lambung dan mikrohabitat lobster pasir (Panulirus homarus) fase Puerulus. Cairan lambung dari sepuluh ekor Puerulus dianalisis dengan metode analisis plankton. Makanan alami di mikrohabitat dikoleksi dengan menyaring seratus liter air laut dari alat tangkap dengan jaring plankton. Makanan alami dalam lambung meliputi fitoplankton dan zooplankton. Fitoplankton terdiri atas satu kelas yaitu bacillariophyceae, tiga ordo yaitu rhabdonematales; naviculales; fragilariales; dan tiga spesies yaitu: Grammatophora marina, Navicula cancellata, dan Synedra radians. Zooplankton terdiri atas kelas oligothriceae ordo choreotrichi spesies Tintinnopsis lobiancoi. Makanan alami di mikrohabitat juga terdiri atas fitoplankton dan zooplankton. Struktur komunitas fitoplankton terdiri atas enam kelas; 26 ordo; dan 39 spesies, sedangkan komunitas zooplankton terdiri atas 10 kelas; 10 ordo; dan 20 spesies. Indeks keanekaragaman makanan alami dalam lambung sebesar 1,39. Rata-rata nilai kelimpahan, indeks keanekaragaman, keseragaman, dan dominansi fitoplankton, serta zooplankton di mikrohabitat berturut-turut 65.744 sel/50 mL; 3,03; 0,82; 0,08; serta 182 sel/50 mL; 1,89; 0,62; 0,3. Grammatophora marina, Navicula cancellata, Synedra radians, dan Tintinnopsis lobiancoi berpotensi sebagai pakan alami larva lobster pasir  (Panulirus homarus).Lombok Island has a high potential to be developed as a central area for lobster farming industry due to the abundance of puerulus in the area. One of the requirements to support the industry is by providing the biological aspect information of spiny lobster (Panulirus homarus) especially its local natural diet during the puerulus phase, which is required to develop a sustainable operation of lobster hatchery. This research was aimed to determine the natural diet in the stomach and microhabitat of puerulus of spiny lobster. The natural diet in the stomach fluid of ten Puerulus was determined using plankton analysis method, while the natural diet in the lobster microhabitat was collected by filtering one hundred liters of seawater in the catching media by using plankton nets. The natural diet in the stomach of puelurus includes phytoplankton and zooplankton. Phytoplankton consisted of one class, bacillariophyceae; three ordines, rhabdonematales, naviculales, fragilariales; and three species, Grammatophora marina, Navicula cancellata, and Synedra radians. Zooplankton consisted of class oligothriceae, ordo choreotrichi, species Tintinnopsis lobiancoi. The natural diet in the microhabitat also consisted of phytoplankton and zooplankton. The community structure of phytoplankton consisted of six classes; 26 ordines; and 39 species, while zooplankton consisted of 10 classes; 10 ordines; and 20 species. The diversity index of the natural diet in the puerulus stomach was classified as moderate H’ 1.39. The averages of abundance, diversity, similarity, and dominance index of phytoplankton and zooplankton in the microhabitat were 65,744 cell/50 mL; 3.03; 0.82; 0.08; and 182 cell/50 mL; 1.89; 0.62; 0.3 respectively. Grammatophora marina, Navicula cancellata, Synedra radians, and Tintinnopsis lobiancoi were found to be dominant and have the potential to be developed as the natural hatchery diet for spiny lobster larvae.